Survey on Effect of Biology Teacher's Variables (Factors) on Academic Performance of Senior Secondary Schools Students in Sokoto Metropolis, Nigeria (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
This research is aimed at finding the effect of biology teacher's variables on the academic performance of senior secondary school students in Sokoto metropolis, Nigeria. Five (5) schools were randomly selected as the sample of the study, including 5 Biology teachers and 200 Biology students, to make the sample of 190 respondents. Using a random sampling technique, two structural questionnaires were used as the instruments for data collection. Frequency count and percentage were the methods used in data analysis. Among the findings drawn in this study are: it was observed that the effects of teachers' qualities with respect to their qualification are high, which modify students' academic performance; most teachers in Sokoto state presently are experienced in their teaching, and this modifies students' academic performance; it was observed that the effect of teachers' qualities with respect to subject-matter knowledge is high. This shows that they have good knowledge of the subject matter. It is recommended that there should be a provision of adequate biology teachers, laboratory equipment, and regular teacher training, seminar, and workshops on the use of instructional materials.